Improving Mathematics Learning Process and Outcomes Using Demonstration Method: Peran Guru dalam Mengatasi Diskriminasi Rasial di Sekolah Dasar - Muhammad Iqbal; Nurlev Avana; Opi Andriani (Academia Open, 2025)
General Background: Mathematics plays a fundamental role in developing logical and systematic thinking skills for elementary students, yet its abstract nature often leads to low engagement and achievement. Specific Background: At SDN 64/II Perumnas 1, third-grade students showed limited understanding of fractions due to lecture-dominated teaching and minimal use of concrete media. Knowledge Gap: While previous studies highlight the benefits of interactive approaches, structured applications of the demonstration method in teaching fractions within the Indonesian primary school context remain underexplored. Aims: This study aimed to improve both the learning process and outcomes in mathematics by applying the demonstration method with concrete, participatory experiences. Results: Conducted as Classroom Action Research in two cycles with 12 students, the findings revealed improvements in teacher performance (from 76.50% to 100%), student engagement (from 0% to 58.33% categorized as “Very Good”), and learning achievement (from 41.66% to 83.33% mastery). Novelty: The study demonstrates that structured use of demonstration—supported by tangible media and active student participation—can effectively transform abstract concepts into meaningful learning experiences within the framework of the Merdeka Curriculum. Implications: These findings suggest that demonstration-based learning enhances conceptual understanding and student participation, providing a practical strategy for primary educators to strengthen mathematics instruction.Highlight : Demonstration method improved learning process and outcomes in fractions. Student engagement shifted from passive to active participation. Learning outcomes increased from 41.66% to 83.33%. Keywords : Demonstration Method, Learning Process, Learning Outcomes, Fractions, Primary Education